2012
DOI: 10.3389/fnmol.2012.00006
|View full text |Cite
|
Sign up to set email alerts
|

The cytokine temporal profile in rat cortex after controlled cortical impact

Abstract: Cerebral inflammatory responses may initiate secondary cascades following traumatic brain injury (TBI). Changes in the expression of both cytokines and chemokines may activate, regulate, and recruit innate and adaptive immune cells associated with secondary degeneration, as well as alter a host of other cellular processes. In this study, we quantified the temporal expression of a large set of inflammatory mediators in rat cortical tissue after brain injury. Following a controlled cortical impact (CCI) on young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 48 publications
8
92
2
Order By: Relevance
“…In head trauma and in cortical stab wound injury, CCL2, produced by activated astrocytes (Glabinski et al 1996), macrophages and endothelial cells (Berman et al 1996), is the most strongly transcribed chemokine in the brain (Stefini et al 2008) and is also found in extracellular fluid (Helmy et al 2011). The protein, which is expressed at a high basal level, is further elevated ∼90-fold (to 1333 pg/mg) following TBI (Dalgard et al 2012). However, when only fold changes are considered, then the ∼236-fold induction of CXCL1 (to 170 pg/mg) is even stronger.…”
Section: Altered Chemokine Expression Following Cns Injurymentioning
confidence: 94%
“…In head trauma and in cortical stab wound injury, CCL2, produced by activated astrocytes (Glabinski et al 1996), macrophages and endothelial cells (Berman et al 1996), is the most strongly transcribed chemokine in the brain (Stefini et al 2008) and is also found in extracellular fluid (Helmy et al 2011). The protein, which is expressed at a high basal level, is further elevated ∼90-fold (to 1333 pg/mg) following TBI (Dalgard et al 2012). However, when only fold changes are considered, then the ∼236-fold induction of CXCL1 (to 170 pg/mg) is even stronger.…”
Section: Altered Chemokine Expression Following Cns Injurymentioning
confidence: 94%
“…Interestingly, on day 2, the composite SNAP scores of the JM4-and PBS-treated groups fell dramatically, only to increase again on day 3. TBI has been associated with delayed activation of CCL2 and CCL20, as well as secondary delayed activation of interleukin (IL)-1β and IL-4 in a rat CCI model, suggesting a temporal relationship between the cytokine profile, their targeted cellular infiltrates, and observed clinical deficits [28]. Exploration of EPO as an immunomodulatory agent has revealed that EPO reduces levels of the proinflammatory cytokines tumor necrosis factor (TNF)-α, IL-1β, interferon (IFN)-γ, IL-6, and intracellular adhesion molecule 1 following EPO treatment in TBI and EAE [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…In this study we designed a novel small, cyclical, EPOderived peptide based on a nonhematopoietic domain within the early sequence [amino acids (AA) [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] of the fulllength EPO molecule that we have named JM4. We evaluated its neuroprotective capabilities on a controlled cortical impact (CCI) model of TBI in mice.…”
Section: Introductionmentioning
confidence: 99%
“…45 CXCL1 protein has been quantified from tissue samples from rat brain after a TBI. 46 In this study, CXCL1, was detected in nearly all dialysates which would be expected given the mechanical injury induced by the implantation of the microdialysis probe. This mechanical injury could cause release from the different cells that release CXCL1.…”
Section: −33mentioning
confidence: 92%